Vnitropodnikové směrnice obchodních korporací - Peštálová, Barbora (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalářská práce je zaměřena na tvorbu vnitropodnikové směrnice pro oblast vnitřního mzdového předpisu zemědělského družstva. První část vymezuje teoretická východiska pro vnitropodnikové směrnice, pracovní poměr, odměňování zaměstnanců, výpočet mzdy a její účtování. Druhá část představuje a analyzuje vybrané družstvo a identifikuje problém. Poslední část se zabývá řešením problému, jehož výsledkem je vytvoření komplexního vnitřního mzdového předpisu.

The bachelor thesis is focused on the creation of an internal company directive for the area of the internal wage regulation of the agricultural cooperative. The first part defines the theoretical basis for internal company directives, the employment relationship, remuneration of employees, calculation of the wage and their accounting. The second part presents and analyzes the selected agricultural cooperative and identifies the problem. The last part deals with the solution of the problem, the result of which is the creation of a comprehensive internal wage regulation.
Accounting Directives for Company
Keywords: vnitropodniková směrnice; mzda; vnitřní mzdový předpis; účetnictví; zaměstnanci; internal company directive; wage; internal wage regulation; accounting; employees